Silencing of a glycosyltransferase-like protein in citrus reduces male and female fertility impacting seed development in self-pollinated fruit - Bennici, Stefania; Alquézar, Berta; Carmona, Lourdes; Distefano, Gaetano; Gentile, Alessandra; Peña, Leandro (Frontiers in Plant Science, 2026)
Citrus species are among the most important fruit tree crops grown worldwide. Their long juvenile period joined with their complex genetic and reproductive characteristics severely hampers genomic studies and the improvement of traits of interest. Among these, seedlessness represents a major fruit quality trait. Genetic engineering is the fastest way to unequivocally characterize the function of citrus genes and to develop better varieties. In this study, two genes from Citrus clementina Hort. ex Tan., CcGLT1 and CcRBP1, that putatively encode a glycosyltransferase-like (GLT) protein and an RNA binding (RBP) family protein, respectively, were characterized as highly expressed in male and female reproductive tissues and then evaluated as candidate genes involved in male and/or female gametic development by silencing them using RNA interference (RNAi) in Carrizo citrange, used as model citrus type easy to transform. Concurrently, the early flowering and fruiting phenotype was induced by ectopic overexpression of the citrus ortholog of the floral integrator FLOWERING LOCUS T gene (FT) which enabled flower and fruit production less than six months after transformation. Histological observations of flower tissues from genetically modified plants showed that silencing CcGLT1 affects pollen performance by reducing pollen germinability and viability which results in an increased rate of ovule abortion resulting in fewer seeds in self-pollinated fruits. Conversely, the silencing of CcRBP1 led to severe alterations in plant growth and development in the transgenic RBP lines preventing the characterization of its role in fertility, which therefore remains unresolved. These results provide useful insights into male and female sterility in citrus for the genetic improvement of commercial varieties aimed to obtain seedless fruits.